Microdosimetric Modelling of Neutron Capture Therapy Effectiveness - Georgiou, Sofia; Kalef-Ezra, John; Kalamara, Antigoni; Karavasilis, Efstratios; Stamatelatos, Ion Evangelos (HNPS Advances in Nuclear Physics, 2024)
Monte Carlo simulations were carried out using the MCNP 6.1 code to predict the energy deposition at microscopic level in in vitro Neutron Capture Therapy studies. Irradiations with neutron beams of energies from 25 meV to 14.2 MeV of small spherical targets loaded with either 1000 ppm natB (200 ppm 10B) or natGd (156 ppm 157Gd) and located at the center of a small phantom were simulated. ENDF/B-VII.1 and TENDL-2017 libraries, as well as INCL4/ABLA and Bertini models were tested using published experimental data as benchmark, i.e. a spherical proportional counter that simulated a 1 μm in diameter tissue equivalent site irradiated with 13.9 MeV neutrons. The methodology, as developed, was applied to assess the microdistribution spectra to the target in terms of yd(y), yF, yD and the kerma to flux ratio for the prediction of the biological response of in vitro cells irradiations.